Metode Design Thinking Dalam Rancangan User Interface Web Smart Grosir Lite - Wiguna, Surya; Supriadi, Fidi; Junaedi, Dani Indra (Jurnal Informatika, Multimedia dan Teknik, 2024)
Smart Grosir Lite is a local wholesale application that provides a modern solution for managing wholesale stores. This research focuses on user interface design issues in the previous Smart Grosir application, such as less appealing designs, low-contrast colors, and some users desiring a simpler interface. The research will utilize the Design Thinking method, following the stages of empathize, define, ideate, prototype, and test, as a technique for designing and evaluating the interaction between users and the software. The goal is to ensure that the software is easy to understand and use. The outcome of this research is a user interface design that is expected to address the shortcomings in the current design and enhance the user experience of Smart Grosir Lite.